ANCA (Antineutrophil Cytoplasmic Antibody)-Associated Pulmonary Vasculitis Causing Pulmonary Artery Stenosis: The Value of Multimodality Imaging in the Clinical Workup. (July 2021) - Zhang, Jing; Wang, Peng; Qin, Chunxia; Zhang, Li; Huang, Daijuan; Li, Yuman; Xie, Mingxing
Abstract : Supplemental Digital Content is available in the text.